Temporally integrated single cell RNA sequencing analysis of controlled and natural primary human DENV-1 infections - Adam T. Waickman; Heather Friberg; Gregory D. Gromowski; Wiriya Rutvisuttinunt; Tao Li; Hayden Siegfried; Kaitlin Victor; Michael K. McCracken; Stefan Fernandez; Anon Srikiatkhachorn; Damon Ellison; Richard G. Jarman; et al. (My University, 2020)
Abstract Controlled dengue human infection studies present an opportunity to address many longstanding questions in the field of flavivirus biology. However, limited data are available on how the immunological and transcriptional response elicited by an attenuated challenge virus compares to that associated with a wild-type DENV infection. To bridge this knowledge gap, we utilized scRNAseq to analyze PBMC from individuals enrolled in a DENV-1 controlled human challenge study and from individuals experiencing a natural primary DENV-1 infection. While both controlled and natural DENV infection resulted in overlapping patterns of inflammatory gene upregulation, natural DENV infection was accompanied with a more pronounced suppression in gene products associated with protein translation and mitochondrial function, principally in monocytes. This suggests that the immune response elicited by controlled and natural primary DENV infection are similar, but that natural DENV infection has a more pronounced impact on basic cellular processes to induce a multi-layered anti-viral state
Keywords: Flavivirus; Mosquito-borne diseases and control